Sustainable Food Production and Safety Protocols in Institutional and Flight Kitchens: A Comparative Study - Binakar , Padmaja; Pathan , Naeem; Padval , Parth; Bhalekar , Omkar; Thakur , Rakesh; Kedar , Priyanka (Journal of Neonatal Surgery, 2025)
The resulting large-scale catering services by institutional and flight kitchen have intensified the question of sustainability and food safety due to the massive production volumes, complicated supply chains, and adherence to production schedules. In this paper, comparative analysis will be done on sustainable food production measures and food safety measures which are implemented on the institutional kitchens (including hospitals, schools, and company canteens) and flight kitchens which are operated by the aviation industry. The dimensions of interest brought up by the study include raw material acquisition, energy and water saving, waste disposal, hygiene, hazard control system, regulatory compliance and training practices among the staff. The data was collected through the structured questionnaires, on-site observations and semi structured interviews with the kitchen managers and food safety officers. The findings showed that flight kitchens have higher level of standardization and adherence to regulations specifically with reference to Hazard Analysis and Critical Control Point (HACCP) adoption, traceability systems and temperature controlled logistics adoption. On the other hand, institutional kitchens are less rigid in sourcing and menu planning that makes new and imbalanced use of sustainable practices, such as local sourcing and separation of waste. The paper identifies that between the sustainability programs and food safety management in the two contexts, there are significant integration loopholes in the sustainability programs. It concludes that a system integrated through environmental sustainability and effective food safety can enhance functioning of the system, reduce environmental footprint and provide safety to the consumers. The research has given effective recommendations to the policy community, food service management, and quality assurance international that would want to increase viable and secure food procurement of large-scaled catering arrangements..